Monthly Carbone Monoxide (CO) Distribution Based on the 2010 MOPITT Satellite Data in Iraq - Rajab, Jasim; Ahmed, Hazim; Moussa, Hussein (Iraqi Journal of Science, 2024)
Carbon monoxide (CO) plays an important indirect greenhouse gases due to its influences on the budgets of hydroxyl radicals (OH) and Ozone (O3). The atmospheric carbon monoxide (CO) observations can only be made on global and continental scales by remote sensing instruments situated in space. One of instrument is the Measurements of Pollution in the Troposphere (MOPITT), which is designed to measure troposphere CO and CH4 by use of a nadir-viewing geometry and was launched aboard the Earth Observing System (EOS) Terra spacecraft on 18 December 1999. Results from the analysis of the retrieved monthly (1ºх1º) spatial grid resolution, from the MOPITT data were utilized to analyze the distribution of CO surface mixing ratio in Iraq for the year 2010. The analysis shows the seasonal variations in the CO surface fluctuate considerably observed between winter and summer. The mean and the standard deviation of monthly CO was (172.076 ± 62.026 ppbv) for the entire study period. The CO value in winter was higher than its values in summer season and its values over Industrial and congested urban zones higher than its values in the rest of regions throughout the year. Maximum values occurred in the northern region (234.105 ppbv) on February at Erbil, were attributed to the increased human activity, geographic nature of the areas and climatic variations. The elevation of CO values on the south-eastern region during the June - November period was due to the emissions from the oil extraction and the burning of agricultural residues in the paddy fields. A greater draws down of the CO occurs over pristine desert environment in the western region (110.047 ppbv) on July at Al Anbar (41.5°log. × 32.5°lat.). The monthly CO surface VMR maps for 2010 were generated using kriging algorithm technique. The MOPITT data and the Satellite measurements are able to measure the increase of the atmosphere CO concentrations over different regions.